“’Sikut’, ‘Sukat’, Menakar Kualitas Diri Manusia Bali, Merajut Literasi Warisan Leluhur: Perspektif Teks Carcan Jadma” - Suardiana, I Wayan; Putra, Ida Bagus Rai (Humanis; Vol 29 No 1 (2025), 2025)
This study views the Carcan Jadma palm leaf text as a literacy that helps someone to know their identity. Qualitative data through library research. Data were obtained through the listening method, accompanied by translation and note-taking techniques, and analyzed through analytical descriptive methods, with inductive techniques. In addition, the data was "dissected" with hermeneutic and semiotic theories to obtain a comprehensive interpretation of meaning. The Carcan Jadma palm leaf text shows that a person's character or nature and luck are correlated with physical characteristics. A person can have these physical characteristics since birth, such as scars, moles, or other congenital defects. The consequence of these physical characteristics is that those who are lucky to have good characteristics and good fortune must maintain them in their daily lives. Those who acquire bad characteristics must change the characteristics that reflect badness with goodness.